Rethinking the Legal Status of Non-Muslims in Islamic Law: Al-Muwāṭinūn and the Constitutional Framework of Citizenship in Indonesia - Hermanto Harun; A. Yuli Tauvani; Nurul Hidayah Tumadi; Rusli Abdul Roni (UIN Sunan Gunung Djati, 2025)
This study aims to examine the relevance of classical Islamic legal categories in defining the status of non-Muslims within the context of Indonesia’s pluralistic and democratic state. The research is motivated by recent debates surrounding the use of the term kāfir (